Variation of resistance response of orchids induced by Rhizoctonia against the infection of Odontoglossum ringspot virus (ORSV) based on percentage of disease development - Fania Nur Izzati; Mahfut Mahfut; Eti Ernawiati; Sri Wahyuningsih (Journal of Sustainability Science and Technology, 2021)
Orchid is one of the largest groups of flowering plants that are in great demand by society. Besides, the various flowers with a long vase life, the price of orchids is also stable and affordable. Phalaenopsis and Dendrobium are the most popular types of orchids. To anticipate this, orchid cultivation needs to be improved. However, orchid cultivation is not always accompanied by the effort of disease prevention, particularly those caused by viruses. The virus that most infects orchids is the Odontoglossum ringspot virus (ORSV). Symptoms that appear on the leaves are chlorosis, mosaic with a pattern of lines, circles, and necrotic rings/rings. Control of viral infections can utilize organisms that are able to induce resistance, namely mycorrhizae. Mycorrhizae will penetrate into the root cortex tissue and provide nutrients for the orchid. Mycorrhizae that are quite often found are Rhizoctonia and are applied by induction to orchids. Induction was undertaken by planting orchids in Rhizoctonia inoculum until anatomically a peloton structure (solid coils) was formed on the orchid roots. The aim of this study was to study the response of orchid plants in the form of percentage incidence and intensity of the disease and the level of plant resistance to ORSV infection in Phalaenopsis amabilis and Dendrobium discolour which had been induced by Rhizoctonia. This research was conducted at the Laboratory of Botany, Biology, FMIPA, Universitas Lampung, using a factorial completely randomized design (CRD). Factor 1 was the type of orchid and factor 2 was mycorrhizal induction, virus inoculation, and a combination of both with 4 replications. The finding indicated that Phalaenopsis amabilis was more susceptible to ORSV infection than Dendrobium discolour based on a higher incidence and intensity of the disease. Mycorrhizal induction and virus inoculation (MAV) in Dendrobium discolour showed an increase of resistance response compared to Phalaenopsis amabilis.